Herbivory enhances the diversity of primary producers in pond ecosystems. Issue 1 (January 2017) - Leibold, Mathew A.; Hall, Spencer R.; Smith, Val H.; Lytle, David A.
Abstract: Diversity of primary producer is often surprisingly high, despite few limiting factors such as nutrients and light to facilitate species coexistence. In theory, the presence of herbivores could increase the diversity of primary producers, resolving this "paradox of the plankton." Little experimental evidence supports this natural enemies hypothesis, but previous tests suffer from several deficiencies. Previous experiments often did not allow for multigeneration effects; utilized low diversity assemblages of herbivores; and limited opportunities for new primary producer and herbivore species to colonize and undergo species sorting that favors some species over others. Using pond plankton, we designed a mesocosm experiment that overcame these problems by allowing more time for interactions over multiple generations, openness to allow new colonists, and manipulated higher diversity of primary producers and grazers than have previous studies. With this design, the presence of zooplankton grazers doubled phytoplankton richness. The additional phytoplankton species in grazed mesocosms were larger, and therefore likely more grazer resistant. Furthermore, phytoplankton richness in grazed mesocosms was similar to that observed in natural ponds whereas it was much lower in mesocosms without grazers. However, stoichiometric imbalance caused by variation in nitrogen : phosphorus ratios and light supply did not alter phytoplankton richness. Therefore, grazers enhanced primary producer richness more strongly than ratios of nutrient supply (even though both grazing and ratios of resource supply altered composition of primary producer assemblages). Taken together, these experimental and field data show that grazing from a diverse assemblage of herbivores greatly elevated richness of phytoplankton producers in pond ecosystems.